תשובה:
# ((5r ^ (- 2)) ^ (- 2)) / ((2r ^ 3) ^ 2) = 1 / (100r ^ 2) # #
הסבר:
אנו יכולים להשתמש כאן בזהות #a ^ (- m) = 1 / a ^ m #.
לפיכך, # ((5r ^ (- - 2)) ^ (- 2)) / ((2r ^ 3) ^ 2) # #
= # (1 / (5r ^ (- 2)) ^ 2) / ((2r ^ 3 * 2 r ^ 3) # #
= # (1 / (5 / r ^ 2) ^ 2) / (4r ^ 6) # #
= # (1 / (25 / r ^ 4)) / (4r ^ 6) # #
= # (r ^ 4 / (25)) / (4r ^ 6) #
= # r ^ 4 / (25 * 4r ^ 6) # #
= # 1 / (100 * r ^ ((6-4)) = 1 / (100r ^ 2) # #
לחלופין ניתן גם להשתמש # (a ^ m) ^ n = a ^ (mn) # עבור כל המספרים השלמים.
לפיכך, # ((5r ^ (- - 2)) ^ (- 2)) / ((2r ^ 3) ^ 2) # #
= # () 5 (- 2) * r ^) (- 2) × (-2))) / ((2r ^ 3 * 2 r ^ 3) # #
= # r ^ 4 / (25 * 4r ^ 6) # #
= # 1 / (100 * r ^ ((6-4)) = 1 / (100r ^ 2) # #